Designing for downsizing: Home-based barriers and facilitators to reduce portion sizes for children - Tang, Tang; Wang, Wenmeng; Vazirian, Marjan; Croden, Fiona; Hetherington, Marion M. (Frontiers in Psychology, 2022)
Evidence confirms that parents know that they should limit non-core foods for their children since these tend to be high in energy density (HED), fat, salt and sugar. However, it is unclear how knowledge of portion size limits, such as the 100 kcal guide from Public Health England are applied in practice. To observe in real-time children’s home food environment related to portion control and to explore with parents their reported portion size strategies, a mixed methods study was designed. Families with children aged 1-5 years were recruited (n = 21) to a three-part study: 1) to complete questionnaires and interviews on household food intake and portion control; 2) to report daily food intake for four days (n = 13) for one parent and their child(ren); 3) to observe home-based food provisioning via videorecording during dinner, breakfast and snack time (n = 6). Although the problem of large portion sizes of HED foods was recognised by mothers, strategies to downsize portions were not necessarily applied at home, as revealed in home observations and diaries. A mismatch between what was observed at home, what was reported in food diaries and what was said in interviews became apparent for some families. Mothers reported the need for greater support and guidance to downsize HED foods since they relied on pre-packaging as a guide to intake. Education and engagement were identified as important parameters for downsizing by mothers. One strategy which could be explored and applied by manufacturers is packaging design to faciliate the 100 kcal guidance using physical and engaging ways to assist parents in downsizing HED foods for their children. To facilitate effective government communication, innovative packaging design can be used to convey clear guidance and to tailor portion size messages for children. Packaging design, alongside government recommendations, can support parents’ goals to achieve healthy eating and can reinforce guidance for portion norms through innovation involving learning, playful engagement, and interaction.